2013
DOI: 10.1002/chir.22208
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Separation of Enantiomers Based on Functional Nucleic Acids Modified Gold Nanoparticles

Abstract: The preparative-scale separation of chiral compounds is vitally important for the pharmaceutical industry and related fields. Herein we report a simple approach for rapid preparative separation of enantiomers using functional nucleic acids modified gold nanoparticles (AuNPs). The separation of DL-tryptophan (DL-Trp) is demonstrated as an example to show the feasibility of the approach. AuNPs modified with enantioselective aptamers were added into a racemic mixture of DL -Trp. The aptamer-specific enantiomer (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Recently, Huang et al. demonstrated the capabilities of aptamer‐based materials in separating amino acid enantiomers. They suggested that stereoisomers of larger molecules such as dipeptides and tripeptides could also be resolved.…”
Section: Chiral Separation Of Small Peptidesmentioning
confidence: 99%
“…Recently, Huang et al. demonstrated the capabilities of aptamer‐based materials in separating amino acid enantiomers. They suggested that stereoisomers of larger molecules such as dipeptides and tripeptides could also be resolved.…”
Section: Chiral Separation Of Small Peptidesmentioning
confidence: 99%
“…In addition, nanostructures possess better chemical stability, low cytotoxicity, significant mechanical strength, and are easily modifiable in terms of their size, shape and surface properties [91,103]. Importantly, NPs enhance the performance of enantioseparation process due to their extremely large s / v ratio (e.g., nanospheres of 10 nm diameter can have a surface area as large as 600 m 2 /cm 3 [121]) that maximizes the amount of binding sites [69,81]. In the following sections we summarize some of the recent applications of different types of nanostructures for the separation of enantiomers.…”
Section: Enantiomeric Separation By Chiral Nanoparticlesmentioning
confidence: 99%
“…Recently, nucleic acid aptamer-functionalized AuNPs were used as chiral selector for the separation of racemic d,l -Trp. The method used centrifugation to separate the precipitate formed by the aptamer-specific enantiomer ( l -Trp) bounded AuNPs (Figure 7) [69]. In another work, Su et al [53] demonstrated the potential of laboratory synthesized chiral N -acetyl- l -Cys-capped AuNPs for high throughput enantiomeric separation of amino acid enantiomers via centrifugation.…”
Section: Enantiomeric Separation By Chiral Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the enantioenrichment efficiency, multistage adsorption was performed further according to literature . After each adsorption stage, the supernatant was analyzed by HPLC and the e.e.…”
mentioning
confidence: 99%